Negotiating Polygamy, Public Morality, and State Authority: Digital Discourse on Governor of DKI Jakarta Regulation Number 2 of 2025 - Wiguno, Moyang Raafi; Fauzi, Muhammad Latif (Jurnal Mediasas: Media Ilmu Syari'ah dan Ahwal Al-Syakhsiyyah, 2026)
This study examines DKI Jakarta Governor Regulation No. 2 of 2025, which regulates the licensing procedures for polygamy among civil servants (Aparatur Sipil Negara/ASN), as an instrument of law as a tool of social engineering within the context of Islamic family law in Indonesia. Employing critical discourse analysis of digital public responses circulating on social media platforms and online news outlets, this research investigates how the regulation is produced, contested, and interpreted in relation to the principles of polygamy in fiqh and the framework of maq??id al-shar?‘ah. The findings reveal a polarized discourse: some actors perceive the regulation as an effort to strengthen morality and governance of marriage among ASN in line with the objective of family protection, while others criticize it as a form of state intervention into the private sphere and the normative authority of Islamic law. This study argues that positioning ASN as policy agents reinforces the state’s legitimacy in managing Islamic family law practices at the bureaucratic level, yet simultaneously generates new tensions between fiqh norms, individual private rights, and modern bureaucratic ethics within Indonesia’s public sphere. Accordingly, this article contributes to the discourse on Islamic family law by demonstrating how the normative authority of fiqh and maq??id al-shar?‘ah is renegotiated through state administrative regulation. [Studi ini menelaah Pergub DKI Jakarta No. 2 Tahun 2025 yang mengatur prosedur perizinan poligami bagi Aparatur Sipil Negara (ASN) sebagai instrumen law as a tool of social engineering dalam konteks hukum keluarga Islam di Indonesia. Dengan menggunakan metode analisis wacana kritis terhadap respons publik digital yang berkembang di media sosial dan pemberitaan daring, penelitian ini mengkaji bagaimana regulasi negara tersebut diproduksi, diperdebatkan, dan dimaknai dalam relasinya dengan prinsip-prinsip poligami dalam fiqh dan kerangka maq??id al-shar?‘ah. Hasil analisis menunjukkan adanya polarisasi wacana: sebagian pihak memandang Pergub sebagai upaya penguatan moralitas dan tata kelola perkawinan ASN yang selaras dengan tujuan perlindungan keluarga, sementara sebagian lain mengkritiknya sebagai bentuk intervensi negara terhadap ruang privat dan otoritas normatif hukum Islam. Studi ini menegaskan bahwa penempatan ASN sebagai agen kebijakan memperkuat legitimasi negara dalam mengelola praktik hukum keluarga Islam pada level birokrasi, namun sekaligus memunculkan ketegangan baru antara norma fiqh, hak privat individu, dan etika birokrasi modern di ruang publik Indonesia. Dengan demikian, artikel ini berkontribusi pada diskursus hukum keluarga Islam dengan menunjukkan bagaimana otoritas normatif fiqh dan maq??id al-shar?‘ah dinegosiasikan ulang melalui regulasi administratif negara.]